Iatrogenic Calyceal Rupture in Patient with Unrecognized Vesicoureteral Reflux - Bae, Woong Jin; Kim, Seol; Choi, Yong Sun; Kim, Su Jin; Cho, Hyuk Jin; Hong, Sung Hoo; Lee, Ji Youl; Hwang, Tae-Kon; Kim, Sae Woong (Urology Journal, 2014)